Matéria escura no Modelo Padrão Supersimétrico Mínimo - Siqueira, Clarissa Martins (2015)
One of the main problems that permeates the Particle Physics and Cosmology is the Dark Matter (DM), which makes up about 26% of the energy content of the Universe. The main evidence pointing to its existence provides us with important features, such as being neutral, stable (with lifetime over the age of the Universe), cold or warm, weakly interacting with Particle Physics Standard Model (SM) particles and sufficiently abundant. The SM does not provide a candidate who meets these characteristics and hence it is necessary to extend it. One of the most sophisticated extensions of the SM is the Supersymmetry, that in addition to solving the problem of DM, explains other unsolved puzzles that are present in SM, among them, the hierarchy and the unification of the gauge couplings. This model implies the inclusion of a new symmetry that puts bosons and fermions in equal footing. The minimal supersymmetric version of the SM is the Minimal Supersymmetric Standard Model (MSSM), whose viable candidate is the neutralino, which is a fermion composed of superpartners of neutral Higgs and gauge bosons. In this work, we performed the neutralino analysis as DM candidate in CMSSM or mSUGRA scenario, which contains 5 free parameters, M0, M1/2, tan , sign(μ) and A0, for two different analyzes. In the first one we varied the M0 and M1/2 parameters for three different values of tan while in the second and third one we varied all parameters except the sign(μ). In this study, we use some computational tools, including, SARAH, SPheno, SSP and Micromegas, in order to obtain DM Relic Abundance and DM scattering cross section in this scenario. We compared our results with the most recent experimental data, namely, we have used Planck satellite data for the relic abundance, LUX and XENON1T (prospect) for the spin-independent scattering cross section and XENON100 for the spin dependent one. We finally analyzed the implications concerning the viability of the MSSM under the light of the DM problem.